2021
DOI: 10.1159/000517625
|View full text |Cite
|
Sign up to set email alerts
|

Novel Speckle Tracking Analysis Showed Excellent Reproducibility for Size and Shape of the Fetal Heart and Good Reproducibility for Strain and Fractional Shortening

Abstract: <b><i>Introduction:</i></b> This study aimed to evaluate reproducibility and agreement of fetal cardiac shape and deformation using <i>FetalHQ</i>. <b><i>Methods:</i></b> Fifty normal fetuses at 20–38 weeks of gestation were evaluated. Two operators independently selected an optimal cardiac cycle using <i>FetalHQ</i><sup>®™</sup>software for speckle tracking analysis. Intra- and interobserver correlation coefficient and limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…Regarding LV systolic parameters (LV volumes, EF and CO), we also report good reproducibility. CO ICC was the lowest regarding LV systolic function, but we only included 24 cases to assess the reproducibility of this parameter, since evaluation of the estimated fetal weight in the same exploration is necessary to calculate CO. On the other hand, biventricular SF showed a poor reproducibility, a finding that has also been reported by other groups [ 55 , 56 ] and that correlates with the poorer reproducibility that we also found for the SI of the different segments of both ventricles. Again, differences in four-chamber-view orientation, methodology and manual tracking could explain our poorer reproducibility results.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding LV systolic parameters (LV volumes, EF and CO), we also report good reproducibility. CO ICC was the lowest regarding LV systolic function, but we only included 24 cases to assess the reproducibility of this parameter, since evaluation of the estimated fetal weight in the same exploration is necessary to calculate CO. On the other hand, biventricular SF showed a poor reproducibility, a finding that has also been reported by other groups [ 55 , 56 ] and that correlates with the poorer reproducibility that we also found for the SI of the different segments of both ventricles. Again, differences in four-chamber-view orientation, methodology and manual tracking could explain our poorer reproducibility results.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, the available studies on 2D STE reproducibility for segmental cardiac morphometric evaluation show discrepant data. While some recent studies [ 55 ] have reported a good reproducibility for biventricular SI (ICC > 0.758), other studies such as ours have shown poorer results, especially for assessing the shape of the basal segments of both ventricles [ 57 ]. We hypothesize that manual adjustment applied for improving the delineation of both ventricles, especially the RV, led to differences in the endocardial delineation, in particular variations of transverse diameters that compute for the SI and FS segmental analysis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…For this Houston study, the same experienced examiner (GRD) performed all ventricular contractility measurements for both the fetuses with EFW <10th centile and for the published normal reference ranges. Measurement variability results for these cardiac measurements have been previously reported 8,34 although the dA/dt method for identifying cardiac systole has not been previously described for fetalHQ software.…”
Section: Strength and Limitationsmentioning
confidence: 99%